2020
DOI: 10.3904/kjim.2020.196
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of coronavirus disease 2019 patients with diarrhea in Daegu

Abstract: Background/Aims: Coronavirus disease 2019 (COVID-19) can reportedly cause gastrointestinal symptoms. Therefore, we investigated the clinical characteristics of COVID-19 patients with diarrhea. Methods: We included 118 COVID-19 patients admitted to a single hospital from February 20 to March 31, 2020. Medical records with clinical characteristics, laboratory data, treatment course, and clinical outcomes were compared based on the presence or absence of diarrhea. Prognostic factors for disease severity and morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 16 publications
(21 reference statements)
0
14
0
9
Order By: Relevance
“…Coronaviruses has been suggested to be transmitted enterically because of adhesion to angiotensin-converting enzyme 2 cell receptors [ 18 , 19 ]. A retrospective study reported that diarrhea was associated with a mild disease course of COVID-19 [ 11 ]. The authors found that patients with diarrhea had lower rates of systemic steroid use and ECMO therapy, milder clinical courses without intensive care unit admission, and lower rates of septic shock and acute respiratory distress syndrome than nondiarrhea patients [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Coronaviruses has been suggested to be transmitted enterically because of adhesion to angiotensin-converting enzyme 2 cell receptors [ 18 , 19 ]. A retrospective study reported that diarrhea was associated with a mild disease course of COVID-19 [ 11 ]. The authors found that patients with diarrhea had lower rates of systemic steroid use and ECMO therapy, milder clinical courses without intensive care unit admission, and lower rates of septic shock and acute respiratory distress syndrome than nondiarrhea patients [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study reported that diarrhea was associated with a mild disease course of COVID-19 [ 11 ]. The authors found that patients with diarrhea had lower rates of systemic steroid use and ECMO therapy, milder clinical courses without intensive care unit admission, and lower rates of septic shock and acute respiratory distress syndrome than nondiarrhea patients [ 11 ]. Other coronavirus infections causing severe acute respiratory syndrome (SARS) were associated with gastrointestinal symptoms and watery diarrhea in approximately 38.4% of patients [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 3-6 days after infection, upper or lower respiratory tract symptoms, fever and diarrhea, or a combination of these, appear (1). Kang et al (2) reported that 45.8% of COVID-19 patients not only have respiratory symptoms, but also gastrointestinal (GI) symptoms, such as lack of appetite, diarrhea, vomiting and abdominal pain. OF 9,696 patients, 988 were reported to exhibit nausea and vomiting.…”
Section: Introductionmentioning
confidence: 99%